The Representation of Multicultural Values in Pearson Big English 6 ELT Textbook: A Discourse Analysis - Suci Rizki Sigid Harahap; Didin Nuruddin Hidayat; Nida Husna; Alek Alek (Jurnal Onoma: Pendidikan, Bahasa, dan Sastra, 2022)
This research aims to examine the visual components of a Pearson primary school English textbook. By applying visual semiotic theory to the visual aspects (Barthes, 1977), this research demonstrates that the EFL textbook has three kinds of multicultural values: respect for other people's traditions, appreciation for women's equal rights, and appreciation for other people's viewpoints. Three photos exemplified respect for other people's traditions, one exemplified gratitude for women's equal rights, and two exemplified appreciation for another person's viewpoint. Additionally, two visual components identified in this research are classified as source culture (SC), four visual elements are classified as universality culture (UC), and there are no visual elements that reflect target culture (TC). The current study discovered that the EFL Pearson textbook for Indonesian primary school continues to have an asymmetric depiction of multicultural values.